Modeling the Release of Antimicrobial Agents (Thymol and Carvacrol) from Two Different Encapsulation Materials - Guarda-Moraga, A; Valenzuela-Bascunan, X; Galotto-Lopez, M (The Korean Society of Food Science and Technology, 2017)
The release of microencapsulated natural antimicrobial (AM) agents (thymol and carvacrol) from two encapsulating matrixes [maltodextrin (MD) and soy protein (SP)] were evaluated for possible use in food packaging coatings. Microcapsules were prepared by oil-in-water (O/W) emulsions at different concentrations (10, 20% for MD and 2, 5% for SP). High encapsulation efficiency ranged from 96 to 99.95% for MD and 93.1 to 100% for SP, with average microcapsule diameters that ranged from 17 to 27.5 and 18.8 to 38 µm, respectively. The release rate with 20% MD-thymol [20MD-T] was faster than with 10% MD-thymol [10MD-T]. Similar results were obtained for carvacrol with the same concentration of MD. Korsmeyer–Peppas and Weibull mathematical models were successfully fitted to the release of the AM agents, describing the Fickian diffusion release of the components. Different release rates were obtained as a function of the chemical nature of the encapsulation material and its concentration. © 2017, The Korean Society of Food Science and Technology and Springer Science+Business Media B.V.